2007
DOI: 10.1007/s11094-007-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the effect of gestagens, antiestrogencytostatics, and androstenes on the viability of tumor and normal cells

Abstract: The hormonal compound with the highest cytostatic activity against MCF-7 tumor cells (human breast cancer, BC) and the lowest activity against normal cells (rat skin fibroblasts) was sought among gestagens, androstenes, and antiestrogencytostatics. It was found that antiestrogencytostatics and androstenes had the highest cytostatic activity against tumor cells whereas gestagens and antiestrogencytostatics were least active against fibroblasts. Studies of the activity of the hormonal compounds in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Previously, in agreement with the above-mentioned data about the low toxicity of androstenes to normal cells, our laboratory showed that 5-AED and DHEA at a concentration of 10 µM do not affect the viability of rat skin fibroblasts [52].…”
Section: Synthesissupporting
confidence: 88%
See 1 more Smart Citation
“…Previously, in agreement with the above-mentioned data about the low toxicity of androstenes to normal cells, our laboratory showed that 5-AED and DHEA at a concentration of 10 µM do not affect the viability of rat skin fibroblasts [52].…”
Section: Synthesissupporting
confidence: 88%
“…The inhibitory effect of androstenes on the chemiluminescence of mononuclear cells, which indicates their anti-ROS and anti-inflammatory activities, develops very fast, within minutes. It was shown earlier that the cytotoxic action of doxorubicin decreases in the presence of androstenes [ 52 ]. The main mechanism of its action is the generation of ROS, and androstenes possibly block/inhibit ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…The oximes were oxidized using pyridinium dichromate (PDC) in Py to produce the corresponding 3-ketones III and V. The structures of all synthesized compounds were derived from physicochemical analyses. 6-Oximes II-V were assigned the E-configuration based on the characteristic resonance of the C7 equatorial proton as a doublet at d 3.33 ppm (J 14.0 and 4.0 Hz) [6,7]. 363 0091-150X/14/4806-0363…”
mentioning
confidence: 99%